What literature debate is not what professionals say about Measuring the ROI of UX Design - Evangelista, Gessé; Zaina, Luciana (Anais da Conferência Latino-Americana de Interação Humano-Computador (CLIHC); 2026: Anais da XII Conferência Latino-Americana de Interação Humano-Computador, 2026)
Measuring the business impact of UX design remains a persistent challenge in both academia and industry, particularly due to the difficulty of linking qualitative user experience evidence to measurable organizational outcomes. Although prior research proposes metrics and frameworks for demonstrating UX value, limited evidence exists on how these approaches align with industry practice. This study investigates the practices, motivations, and challenges associated with measuring the Return on Investment (ROI) of UX design. To address this objective, we conducted a rapid literature review and an online questionnaire with UX professionals. The findings from both sources were analyzed using thematic analysis, enabling a comparative examination of academic perspectives and practitioner experiences. The results reveal differences between conceptual measurement models proposed in the literature and the operational metrics used in practice. While research often emphasizes structured analytical frameworks linking UX improvements to business performance, practitioners rely mainly on pragmatic indicators derived from product analytics systems. The findings also highlight challenges related to causal attribution and organizational data integration, as well as motivations associated with legitimizing UX within business decision-making processes. By triangulating evidence from research and practice, this study contributes to a better understanding of how UX ROI measurement operates in real-world contexts and highlights opportunities for developing measurement approaches that better reflect organizational realities.